MUALAF DI MINAHASA : KESALEHAN BERAGAMA DAN PILIHAN POLITIK - Almunauwar Bin Rusli (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2020)
This article discusses the mualaf groups in North Minahasa as a Christian bastion : Islam (37,934) and Christians (200,213). Minahasa and Christianity are inseparable from ideology. Islam has inspiring Mualaf life since the beginning of hijrah movement on television. This article employs a qualitative descriptive method with sociological approach. Participatory observations, in-depth interviews and literature studies were conducted at Desa Warisa. The result of research shows that the majority of mualaf groups comes from Minahasan ethnic (Tonsea) and Sanger. They live as farmers, housewives and laborers. They convert from Christianity to Islam because of marriage system. They got Islamic teachings from Insan Kawanua with Ronald Lambey (Muhammad Hamzah). Mualaf is a form of piety to go to heaven by implementing the shari’a as well as being mubaligh in Minahasa. They are not willing to choose political leaders from Christianity because of the injustice problems. They used Majelis Taklim and social media like facebook and whatsapp in order to have a prime position in identity politics battles in Minahasa.